Accelerating AAV biosafety and characterization decisions with validated NGS workflows - Andrew Hillhouse (Cell and Gene Therapy Insights, 2026)
Confirming product identity, genome integrity and freedom from adventitious agents requires a single test to hold up across genomes as small as an AAV vector and as large as a human genome, against regulatory guidance that continues to evolve (ICH Q5A(R2)). Here is how FUJIFILM Biotechnologies built validated NGS workflows covering library preparation, genome integrity, sensitivity testing and adventitious agent detection, cutting biosafety testing turnaround from up to 8 weeks to 1–2 weeks.